Women as political socialization agents: A study of gendered political mobilization in Indonesia’s 2024 election (Case of PKS in Deli Serdang) - Yanti, Delfi; Harahap, Elly Warnisyah; Aminuddin, Aminuddin; Reksa, M. Angga (Universitas Muhammadiyah Malang, 2026)
Women’s political participation has become an important issue in contemporary democratic studies, particularly in emerging democracies such as Indonesia, where elections serve as a key mechanism for citizen engagement. However, most existing studies still conceptualize political socialization as a passive, cultural, and family-based process. There is limited attention to how political parties actively mobilize women as strategic agents of political socialization, especially at the local level. This study aims to analyze the role of women as political socialization agents in Indonesia’s 2024 election, focusing on gendered political mobilization within the Prosperous Justice Party (PKS) in Deli Serdang Regency. This research employs a qualitative approach with a grounded perspective. Data were collected through in-depth interviews and field observations, supported by secondary data from official documents and academic literature. Informants consisted of female party elites, members, and cadres selected through purposive sampling. Data were analyzed using thematic analysis. The findings show that women in PKS play an active and strategic role through organizational consolidation, community-based engagement, and digital political campaigns. Their involvement contributes to increasing women’s political participation and shaping voter preferences. However, an ambivalence is identified between empowerment and instrumentalization, where women’s participation simultaneously reflects inclusion and serves electoral interests. This study contributes by reconceptualizing political socialization as an active and organized process driven by political actors and by advancing the concept of gendered political mobilization in local democratic contexts. Partisipasi politik perempuan menjadi isu penting dalam studi demokrasi kontemporer, khususnya di negara berkembang seperti Indonesia, di mana pemilu merupakan sarana utama keterlibatan warga negara. Namun, sebagian besar kajian masih memandang sosialisasi politik sebagai proses yang pasif, kultural, dan berbasis keluarga. Penelitian yang menyoroti bagaimana partai politik secara aktif memobilisasi perempuan sebagai agen strategis sosialisasi politik, khususnya di tingkat lokal, masih terbatas. Penelitian ini bertujuan untuk menganalisis peran perempuan sebagai agen sosialisasi politik pada Pemilu 2024, dengan fokus pada mobilisasi politik berbasis gender di Partai Keadilan Sejahtera (PKS) Kabupaten Deli Serdang. Penelitian ini menggunakan pendekatan kualitatif dengan perspektif grounded. Data dikumpulkan melalui wawancara mendalam dan observasi lapangan, serta didukung oleh data sekunder berupa dokumen resmi dan literatur ilmiah. Informan terdiri dari pengurus, anggota, dan kader perempuan PKS yang dipilih secara purposive. Analisis data menggunakan teknik thematic analysis. Hasil penelitian menunjukkan bahwa perempuan PKS berperan aktif dan strategis melalui konsolidasi organisasi, pemberdayaan komunitas, serta kampanye politik digital. Peran ini berkontribusi dalam meningkatkan partisipasi politik perempuan dan memengaruhi preferensi pemilih. Namun, ditemukan ambivalensi antara pemberdayaan dan instrumentalisasi dalam keterlibatan perempuan. Penelitian ini berkontribusi dalam merekonseptualisasi sosialisasi politik sebagai proses aktif dan terorganisir serta memperkuat konsep mobilisasi politik berbasis gender dalam konteks demokrasi lokal.